One-stop integrated service accountability at Majene district court - Dian Untung Patintinga; Asrullah Asrullah; ika Novitasaric Novitasaric (Indonesia Prime, 2021)
The Supreme Court as part of the government in the judicial field has also tried to make improvements to realize its vision to become the Supreme Indonesian Judicial Body, one of whose efforts is oriented towards excellent public services. To achieve this vision, the Supreme Court has outlined it in several missions where one of the missions that has been established is to provide equitable legal services to justice seekers. Based on the results of preliminary observations, it shows the number of criminal cases entered in 2019 amounted to 4,326 cases that can be resolved properly. While the number of civil cases entered in 2019 amounted to 67 cases with 54 cases resolved properly and 13 cases unresolved